Cloud computing for dummies ebook - Hurwitz, Judith S. (2020)
Get your head—and your business—into the Cloud  Cloud computing is no longer just a clever new toy in the world of IT infrastructure. Despite the nebulous name, it's become a real and important part of our information architecture—and tech professionals who ignore it or try to skim their way through risk falling behind rapidly. The new edition of  Cloud Computing For Dummies  gets you up to speed fast, clarifying your Cloud options, showing you where can save you time and money, giving you ways to frame your decisions, and helping you avoid weeks of research.  In a friendly, easy-to-follow style,  Cloud Computing For Dummies, 2nd Edition  demystifies the Cloud's virtual landscape, breaking up a complex and multi-layered topic into simple explanations that will make the various benefits clear and ultimately guide you toward making the most appropriate choices for your organization. Know the business case for the Cloud  Understand hybrid and multi-cloud options  Develop your Cloud strategy  Get tips on best practices  The Cloud is everywhere, and it can deliver amazing benefits to our lives and businesses. Get a much clearer vision of exactly how with  Cloud Computing For Dummies —and you'll begin to see that the sky really is the limit!